Verification of Nonlinear Characteristics of Radar Angular Glint by Surrogate Data Method - Zhang, Jin; Li, Zhiping; Zheng, Cheng; Miao, Jungang (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, we present a nontrivial verification of nonlinear characteristics of angular glint by the surrogate data method. Glint is a key cause of target loss in radar detections. Prediction and suppression of glint is a hot topic. Firstly, glint data of a typical target are calculated by GRECO method for two motions. As glint is calculated by quadric surface calculations, it is nonlinear in mathematical nature. The surrogate data method is explained and workflow is summarized to verify the nonlinear traits of glint. Surrogate methods of phase randomized Fourier transform and amplitude adjusted Fourier transform are illustrated. Test statistics of higher order moments and time reversibility are given. Lorenz model is simulated as a standard nonlinear model to verify effectiveness of workflow, and nonlinear verification criteria are drawn. A new parameter is designed to measure the powerfulness of nonlinearity. Finally, nonlinear verifications for the two angular glint series are given. Results are illustrated in figures and data and they agree with nonlinear criterion. This paper lays the foundations for chaotic verifications of glint.